PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVa SDN 005 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Saputra, Dedy; Noviana, Eddy; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is cause is the low social studies learning outcomes with average grade 58,5. While the udue of minimum criteria of completenes is 65 this researches is classroom action research (CAR). That suppose to incriasing of the social studies students learning outcomes of fourth grade of SDN 005 Sungai Segajah Kecamatan Kubu in Rokan Hilir district. The formula of the problem is does the aplication of cooperative learning model type Think Pair Share (TPS) can inprove the social studies studen learning outcomes of fourth grade SDN 005 Sungai Segajah Kecamatan Kubu in Kabupaten Rokan Hilir. Before dairy CAR the students good average grade 58,5. Ard after CAR the average grade in create is 65,90% whereas on the scord cycle the average grade increase is 70,22%. So the improvement of students learning out comes from the bassed score to cycle I increase about 16,02%. whereas from based score to cycle II increase about 63,02%. The activity of the student in first cycle with an average grade 62,5% and the scord cycle is about 79,16%. The activity of the teacher on the first cycle with an average grade 66,66% and the secord cycle is about 91,66%. The result of this research is the application of cooperative learning model type Think Pair Share (TPS) can increase the social studies students learning outcomes at fourth brade of SDN 005 Sungai Segajah Kecamatan Kubu in Kabupaten Rokan Hilir.Keywords : think pair share (TPS), social studies learning outcom